Marketing strategies for Islamic bank products amid competition with digital fintech - Natasya, Adelia; Nurbaiti, Nurbaiti; Nasution, Juliana (LPMP Imperium, 2025)
This study aims to identify the marketing strategies employed by Islamic banks that can operate synergistically, creating an integration model aligned with Sharia principles in the context of digital fintech. The research utilizes a qualitative descriptive approach to explore the marketing strategies of Islamic bank products amidst competition from digital fintech companies. The subject of the study is Bank Syariah Indonesia (BSI) KCP Cemara Asri. Data collection methods include interviews, observations, and documentation. The collected data was analyzed using transcripts from interviews and notes from observations. The findings indicate that Bank Syariah Indonesia (BSI) has successfully implemented an effective digital marketing strategy using the BSI Mobile application, website, and social media platforms. This approach targets millennial customers and enhances the public's understanding of Islamic banking products and digital banking services. Important factors contributing to the success of this strategy include direct education initiatives and institutional activities, as well as a strong focus on transaction security and customer data protection. Public interest statements This research aims to provide valuable insights into Islamic banks' marketing strategies for facing digital fintech competition, contributing to better industry practices and supporting financial inclusion.